Flame-retardant polyamide resin composition and molded article made thereof
The flame-retardant polyamide resin composition, formulated with specific polyamide resins and additives, addresses the limitations of existing compositions by enhancing flame retardancy, toughness, and heat-discoloration resistance, resulting in high-quality molded parts with excellent snap fit and moldability.
Patent Information
- Application Number
- JP2021543701
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-09-02
- Filing Date
- 2020-08-21
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2040-08-21
AI Technical Summary
Existing non-halogen flame-retardant polyamide resin compositions, particularly those using melamine cyanurate, suffer from poor dispersibility, degradation of mechanical properties, bleeding, and sublimation issues, which compromise the flame retardancy and surface quality of molded parts.
A flame-retardant polyamide resin composition is developed, comprising 97.5 to 94 parts by mass of polyamide resin and 2.5 to 6 parts by mass of melamine cyanurate, along with specific additives such as phosphorus-based antioxidants, hindered phenol-based antioxidants, and fatty acid metal salt lubricants, to enhance flame retardancy, toughness, and heat-discoloration resistance.
The composition achieves excellent heat-resistant discoloration, moldability, and snap fit properties, maintaining high flame retardancy without bleeding, and ensuring the quality of molded parts, particularly those with thin portions like hinges.
Smart Images

Figure 0007647560000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a non-halogen flame-retardant polyamide resin composition, more particularly to a non-halogen flame-retardant polyamide resin composition having high flame retardancy, good toughness and excellent resistance to heat discoloration. [Background technology]
[0002] Polyamide resins are used in various fields such as electric and electronic parts, automobile parts, etc., taking advantage of their excellent mechanical properties, electrical properties, chemical resistance, etc. In these fields, when flame retardancy is required to be imparted by an unreinforced and non-halogen flame retardant, melamine cyanurate is used as the flame retardant (for example, Patent Documents 1 and 2). However, melamine cyanurate has the following drawbacks: it has poor dispersibility in polyamide resins, which reduces the mechanical properties of the polyamide resins; it bleeds when incorporated in large amounts; it is easily decomposed into melamine and cyanuric acid by thermal decomposition and sublimes, and the sublimated melamine and cyanuric acid tend to cause silver streaks on the surface of molded articles during molding and to contaminate the surface of the mold.
[0003] In recent years, various requirements for electrical / electronic parts, automotive parts, etc. have been increasing. For parts with thin sections such as hinges, flame retardancy of UL94 V-0 level at a thickness of 0.4 mm is required. Higher levels are also being desired, including no bleeding of flame retardants, heat discoloration resistance, moldability, and even snap-fitting of parts. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Special Publication No. 58-25379 [Patent Document 2] Special Publication No. 58-35541 Summary of the Invention [Problem to be solved by the invention]
[0005] The present invention aims to provide a flame-retardant polyamide resin composition which is suitable for molded parts having thin-walled parts such as hinge parts, has flame retardancy of UL94 V-0 level at a thickness of 0.4 mm, does not cause bleeding of the flame retardant, and has excellent heat discoloration resistance, moldability, snap-fit properties of parts, etc. [Means for solving the problem]
[0006] The present inventors have conducted extensive research to solve the above problems and have completed the present invention.
[0007] That is, the present invention has the following configuration. [1] A flame-retardant polyamide resin composition comprising 97.5 to 94 parts by mass of a polyamide resin (A) and 2.5 to 6 parts by mass of a melamine cyanurate (B), wherein the polyamide resin (A) comprises 50 to 80 parts by mass of a polyamide 66 resin (A-1) and 15 to 45 parts by mass of a polyamide 6 resin (A-2), and further comprising 0.01 to 1 part by mass of a phosphorus-based antioxidant (C), 0.01 to 1 part by mass of a hindered phenol-based antioxidant (D), and 0.05 to 1 part by mass of a fatty acid metal salt-based lubricant (E) relative to 100 parts by mass in total of the components (A) and (B). [2] The flame-retardant polyamide resin composition according to [1], wherein the phosphorus-based antioxidant (C) is a compound having a pentaerythritol diphosphite skeleton. [3] The flame-retardant polyamide resin composition according to [1] or [2], wherein the fatty acid metal salt-based lubricant (E) is a metal salt of an aliphatic carboxylic acid having 22 to 30 carbon atoms. [4] A molded article having a hinge portion, comprising the flame-retardant polyamide resin composition according to any one of [1] to [3]. [5] The molded product according to [4], wherein the molded product having the hinge portion is a ferrite core cover, a cable tie, or an electrical wiring protection member. Effect of the Invention
[0008] The flame-retardant polyamide resin composition of the present invention not only has excellent heat discoloration resistance and moldability, but also provides molded articles having appropriate elasticity and high breaking strength, resulting in excellent snap-fit properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The present invention will be specifically described below. [Polyamide resin (A)] The polyamide resin (A) in the present invention is not particularly limited as long as it is a polymer having an amide bond (-NHCO-) in the main chain. The polyamide resin (A) is preferably crystalline, and examples thereof include polyamide 6 (PA6), polyamide 66 (PA66), polyamide 46 (PA46), polyamide 11 (PA11), polyamide 12 (PA12), polyamide 610 (PA610), polyamide 612 (PA612), polymetaxylylene adipamide (PAMXD6), hexamethylenediamine-terephthalic acid polymer (PA6T), hexamethylenediamine-terephthalic acid and adipic acid polymer (PA6T / 66), hexamethylenediamine-terephthalic acid and ε Examples of the polyamide resin include, but are not limited to, crystalline polyamide resins such as caprolactam copolymer (PA6T / 6), trimethylhexamethylenediamine-terephthalic acid polymer (PATMD-T), metaxylylenediamine, adipic acid, and isophthalic acid copolymer (PAMXD6 / MXDI), trihexamethylenediamine, terephthalic acid, and ε-caprolactam copolymer (PATMDT / 6), and diaminodicyclohexylenemethane, isophthalic acid, and lauryllactam copolymer, or blends thereof.
[0010] The blending amount (content) of the polyamide resin (A) is 97.5 to 94 parts by mass when the total of the polyamide resin (A) and the melamine cyanurate (B) is 100 parts by mass. When the blending amount of the polyamide resin (A) is within this range, the composition can be provided with suppressed bleeding of the flame retardant and with high flame retardancy. The blending amount (content) of the polyamide resin (A) is preferably 97 to 94.5 parts by mass, more preferably 97 to 95 parts by mass. In the flame-retardant polyamide resin composition of the present invention, the blending amount of each component is the content as it is.
[0011] In view of excellent moldability, melt flowability, and flame retardancy, the polyamide resin (A) in the present invention is preferably a mixture of polyamide 66 resin (A-1) and polyamide 6 resin (A-2).
[0012] The polyamide 66 resin (A-1) in the present invention may be a polyamide 66 resin obtained by polycondensation of adipic acid and hexamethylenediamine as raw materials. The relative viscosity of the polyamide 66 resin (A-1) is preferably 2.2 to 3.5, as measured in accordance with JIS K6810 at a concentration of 1% in 98% sulfuric acid and at a temperature of 25°C. If the relative viscosity is less than 2.2, the mechanical properties tend to decrease, and if it exceeds 3.5, the melt fluidity tends to be insufficient. The relative viscosity of the polyamide 66 resin (A-1) is more preferably 2.3 to 3.0.
[0013] The terminal amino group concentration of the polyamide 66 resin (A-1) is not particularly limited, but is preferably 50 to 90 eq / ton, and more preferably 60 to 80 eq / ton in terms of heat discoloration resistance.
[0014] The blending amount of polyamide 66 resin (A-1) is preferably 50 to 80 parts by mass when the total of polyamide resin (A) and melamine cyanurate (B) is 100 parts by mass. If the blending amount of polyamide 66 resin (A-1) exceeds 80 parts by mass, the hinge property (snap-fit property) decreases, and if it is less than 50 parts by mass, the moldability tends to decrease. The blending amount of polyamide 66 resin (A-1) is more preferably 75 to 55 parts by mass from the viewpoint of the balance between snap-fit property and moldability.
[0015] The polyamide 6 resin (A-2) in the present invention is a polyamide 6 resin obtained by polycondensation using ε-caprolactam as a raw material. The relative viscosity of the polyamide 6 resin (A-2) is preferably 2.0 to 4.5, as measured in 98% sulfuric acid at a concentration of 1% and at a temperature of 25° C. according to JIS K6810. If the relative viscosity is less than 2.0, the mechanical properties are likely to decrease, and if it exceeds 4.5, the flame retardancy is likely to be impaired. The relative viscosity of the polyamide 6 resin (A-2) is more preferably 2.2 to 3.5.
[0016] The terminal amino group concentration of the polyamide 6 resin (A-2) is not particularly limited, but is preferably 50 to 90 eq / ton, and more preferably 60 to 80 eq / ton in terms of heat discoloration resistance.
[0017] The blending amount of polyamide 6 resin (A-2) is preferably 15 to 45 parts by mass when the total of polyamide resin (A) and melamine cyanurate (B) is 100 parts by mass. If the blending amount of polyamide 6 resin (A-2) is less than 15 parts by mass, the hinge property (snap-fit property) is likely to decrease, and if it exceeds 45 parts by mass, the moldability is likely to decrease. The blending amount of polyamide 6 resin (A-2) is more preferably 20 to 40 parts by mass from the viewpoint of the balance between snap-fit property and moldability.
[0018] In order to improve the appearance of the molded article, an amorphous polyamide resin (A-3) can also be blended. Examples of amorphous polyamide resins include polymers, copolymers, or blends obtained by polycondensation of diamines such as 4,4'-diamino-3,3'-dimethyldicyclohexylmethane (CA), 4,4'-diaminodicyclohexylmethane (PACM), metaxylylenediamine (MXD), trimethylhexamethylenediamine (TMD), isophoronediamine (IA), 4,4'-diaminodicyclohexylpropane (PACP), and hexamethylenediamine, and dicarboxylic acids such as terphthalic acid, isophthalic acid, adipic acid, sebacic acid, and dodecanedicarboxylic acid, and lactams such as caprolactam and lauryllactam.
[0019] [Melamine cyanurate (B)] The melamine cyanurate (B) in the present invention is preferably an equimolar reaction product of cyanuric acid and melamine. In addition, a part of the amino group or hydroxyl group in the melamine cyanurate may be substituted with another substituent. The melamine cyanurate can be obtained, for example, by mixing an aqueous solution of cyanuric acid and an aqueous solution of melamine, reacting them under stirring at 90 to 100°C, and filtering the resulting precipitate. The obtained solid can be used as it is, but it is preferable to use it after pulverizing it as necessary. There is no particular restriction on the particle size, but from the viewpoint of flame retardancy and toughness, the average particle size is preferably 0.5 to 20 μm, more preferably 1 to 15 μm.
[0020] The blending amount (content) of the melamine cyanurate (B) is 2.5 to 6 parts by mass when the total of the polyamide resin (A) and the melamine cyanurate (B) is 100 parts by mass. From the viewpoint of flame retardancy, it is 2.5 parts by mass or more, and from the viewpoint of toughness, it is 6 parts by mass or less. It is more preferably 3 to 5.5 parts by mass, and further preferably 3 to 5 parts by mass. In the present invention, toughness is a property related to snap-fit properties.
[0021] [Phosphorus-based antioxidants (C)] The phosphorus-based antioxidant (C) in the present invention may be an inorganic compound or an organic compound, and is not particularly limited.Preferred phosphorus-based compounds include inorganic phosphates such as monosodium phosphate, disodium phosphate, trisodium phosphate, sodium phosphite, calcium phosphite, magnesium phosphite, and manganese phosphite, triphenyl phosphite, trioctadecyl phosphite, tridecyl phosphite, triisodecyl phosphite, trinonylphenyl phosphite, diphenylisodecyl phosphite, diphenyl alkyl phosphite, phenyl dialkyl phosphite, tris(nonylphenyl) phosphite, trilauryl phosphite, distearyl pentaerythritol diphosphite, tris(2,4-di-tert-butylphenyl) phosphite, diisodecyl pentaerythritol diphosphite, bis(2,4-di-tert-butylphenyl) pentaerythritol diphosphite, bis(2,6-di-tert-butyl-4-methylphenyl) pentaerythritol diphosphite, di Isodecyloxypentaerythritol diphosphite, bis(2,4-di-tert-butyl-6-methylphenyl)pentaerythritol diphosphite, bis(2,4,6-tris(tert-butylphenyl))pentaerythritol diphosphite, tristearyl sorbitol triphosphite, tetrakis(2,4-di-tert-butylphenyl)-4,4'-biphenylene diphosphonite, 6-isooctyloxy-2,4,8,10-tetrakis(2,4-di-tert-butylphenyl)-4,4'-biphenylene diphosphonite Examples include tra-tert-butyl-12H-dibenzo[d,g]-1,3,2-dioxaphosphocin, 6-fluoro-2,4,8,10-tetra-tert-butyl-12-methyl-dibenzo[d,g]-1,3,2-dioxaphosphocin, bis(2,4-di-tert-butyl-6-methylphenyl)methyl phosphite, and bis(2,4-di-tert-butyl-6-methylphenyl)ethyl phosphite, which are added to improve resistance to heat discoloration.
[0022] The phosphorus-based antioxidant (C) is preferably a phosphite compound, and among the phosphite compounds, a compound having a pentaerythritol diphosphite skeleton is preferred. Specifically, those having a pentaerythritol diphosphite skeleton and a molecular weight of about 600 to 800, such as bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite ("ADK STAB PEP-36", molecular weight 633), bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite ("ADK STAB PEP-24G", molecular weight 604), distearyl pentaerythritol diphosphite ("ADK STAB PEP-8", molecular weight 733), and bis(nonylphenyl)pentaerythritol diphosphite ("ADK STAB PEP-4C", molecular weight 633), are particularly preferred because they can further improve releasability without reducing flame retardancy and are also suitable for snap-fit properties.
[0023] The blending amount (content) of the phosphorus-based antioxidant (C) is 0.01 to 1 part by mass when the total of the polyamide resin (A) and the melamine cyanurate (B) is 100 parts by mass. When the blending amount of the phosphorus-based antioxidant (C) is within this range, discoloration during extrusion processing can be suppressed, and secondary oxidative deterioration caused by radicals derived from phosphorus can be prevented. The blending amount of the phosphorus-based antioxidant (C) is preferably 0.1 to 0.5 parts by mass.
[0024] [Hindered phenol antioxidants (D)] Examples of the hindered phenol-based antioxidant (D) in the present invention include N,N'-hexamethylene-bis-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionamide, bis(3,3-bis-(4'-hydroxy-3'-tert-butylphenyl)butanoic acid) glycol ester, 2,1'-thioethyl bis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 4,4'-butylidene-bis(3-methyl-6-tert-butylphenol), triethylene glycol-3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate "SONGNOX2450", molecular weight 633), and mixtures of two or more of these can also be used.
[0025] The amount (content) of the hindered phenol-based antioxidant (D) is 0.01 to 1 part by mass when the total of the polyamide resin (A) and the melamine cyanurate (B) is 100 parts by mass. When the amount of the hindered phenol-based antioxidant (D) is within this range, it is possible to prevent oxidative deterioration over time with an appropriate amount according to the coordinate bond of the polyamide composition. The amount of the hindered phenol-based antioxidant (D) is preferably 0.1 to 0.5 parts by mass.
[0026] [Fatty acid metal salt lubricant (E)] The fatty acid metal salt-based lubricant (E) in the present invention may be a metal salt of a fatty acid having 12 to 40 carbon atoms, such as stearic acid, palmitic acid, behenic acid, erucic acid, oleic acid, lauric acid, and montanic acid. Among them, a metal salt of an aliphatic carboxylic acid having 22 to 30 carbon atoms is preferred, and an alkali metal or alkaline earth metal salt of behenic acid, lignoceric acid, montanic acid, etc. is more preferred in terms of releasability. Examples of the alkali metal or alkaline earth metal include lithium, sodium, magnesium, and calcium salts.
[0027] The amount (content) of the fatty acid metal salt lubricant (E) is 0.05 to 1 part by mass when the total of the polyamide resin (A) and the melamine cyanurate (B) is 100 parts by mass. If it is less than 0.05 part by mass, the mold releasability may decrease, and if it exceeds 1 part by mass, the flame retardancy may decrease. The amount of the fatty acid metal salt lubricant (E) is preferably 0.1 to 0.8 parts by mass.
[0028] [Other ingredients] In addition to the above-mentioned (A), (B), (C), (D), and (E), other components, such as colorants such as pigments and dyes, additives such as heat stabilizers, weather resistance improvers, nucleating agents, plasticizers, release agents, and antistatic agents, other resin polymers, etc., may be added to the flame-retardant polyamide resin composition of the present invention, so long as the object of the present invention is not impaired. The total amount of the above-mentioned (A), (B), (C), (D), and (E) components in the flame-retardant polyamide resin composition of the present invention is preferably 80% by mass or more, more preferably 90% by mass or more, and even more preferably 95% by mass or more.
[0029] Suitable molded parts obtainable using the flame-retardant polyamide resin composition of the present invention are molded articles having a hinge portion, specifically molded parts having a thin hinge portion such as connectors, coil bobbins, breakers, electromagnetic switches, holders, plugs, sockets, switches, cases, and covers used in the fields of electric / electronic parts, automobile parts, and the like, and more specifically parts requiring heat discoloration resistance and snap fit properties such as ferrite core covers, cable ties, and electric wiring protection members.
[0030] The method for producing the flame-retardant polyamide resin composition of the present invention is not particularly limited, and a general single-screw extruder, twin-screw extruder, pressure kneader, etc. can be used as a kneading device, but a twin-screw extruder is particularly preferred in the present invention. In one embodiment, the above-mentioned (A), (B), (C), (D), (E), and, depending on the application, a pigment, etc. are mixed and charged into a twin-screw extruder. By uniformly kneading with the twin-screw extruder, a polyamide-based resin composition excellent in toughness and flame retardancy can be produced. The kneading temperature of the twin-screw extruder is preferably 220 to 300°C, and the kneading time is preferably about 2 to 15 minutes. EXAMPLES
[0031] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way.
[0032] The following components were used. Polyamide resin (A); A1: Polyamide 66 (RV=2.8) Vydyne 21FSR (manufactured by Ascend), melting point 265°C A2: Polyamide 6 (RV=2.6) ZISAMIDE TP4208 (manufactured by Shuseisha), melting point 225°C
[0033] Melamine cyanurate (B); B: MC6000 (Nissan Chemical Co., Ltd.)
[0034] Phosphorus-based antioxidants (C); C1: Adeka STAB PEP-36 (ADEKA Corporation) C2: Adeka STAB 3010 (triisodecyl phosphite) (manufactured by ADEKA Corporation)
[0035] Hindered phenolic antioxidants (D); D: SONGNOX2450 (Songwon International Japan)
[0036] Fatty acid metal salt-based lubricants (E); E1: Calcium montanate CS-8-CP (manufactured by Nitto Kasei Kogyo Co., Ltd.) Other release agents; E2: Aliphatic ester Recorb WE-40 (Clariant Japan Co., Ltd.)
[0037] [Examples 1 to 6 (Example 6 is a reference example) , Comparative Examples 1 to 4] The evaluation samples were produced by weighing out the raw materials in the blending ratio of the polyamide resin composition shown in Table 1, mixing them in a tumbler, and then feeding them into a twin-screw extruder. The temperature of the twin-screw extruder was set to 250°C to 300°C, and the kneading time was 5 to 10 minutes. The obtained pellets were molded into various evaluation samples using an injection molding machine. The cylinder temperature of the injection molding machine was set to 250°C to 290°C, and the mold temperature was set to 80°C.
[0038] The various evaluation methods are as follows. The evaluation results are shown in Table 1. 1. Relative Viscosity [RV] of Polyamide Resin (98% Sulfuric Acid Solution Method) The viscosity was measured using an Ubbelohde viscosity tube at 25° C. in a 98% by weight sulfuric acid solution with a polyamide resin concentration of 1 g / dL. 2. Melting point of polyamide resin The measurement was performed using a differential scanning calorimeter EXSTAR 6000 manufactured by Seiko Instruments Inc. at a temperature increase rate of 20° C. / min to determine the endothermic peak temperature. 3. Snap fit properties (tensile strength, tensile elongation): Measured according to ISO527. 4. Flammability: Measured according to UL94 vertical flame test. V-0 indicates the highest flame retardancy. 5. Bleeding properties: A 100 mm x 100 mm molded product with a thickness of 2 mm was placed in a thermo-hygrostat set at 80°C and 95% RH for 96 hours, and this was repeated at least twice. The product was then returned to room temperature and visually inspected with a stereomicroscope to see if there were any precipitates on the surface. 6. Thermal discoloration: The color difference (ΔE) between the pellets after leaving them in an oven at 120° C. for 8 hours and the pellets before and after the treatment was calculated. 7. Moldability: Using a mold equipped with a mold release force measuring device, molding was carried out under the above molding temperature conditions, and the mold release force was measured from the 31st shot to the 35th shot to obtain the mold release resistance value.
[0039] [Table 1]
[0040] In Examples 1 to 6, the tensile elongation is 20% or more, and the inherent toughness of the polyamide resin (A) is maintained. In addition, the tensile strength is not significantly impaired, so good snap-fit properties are expected to be obtained. In terms of flame retardancy at a thickness of 0.4 mm, Examples 1 to 6 also achieved a V-0 rating. In terms of thermal discoloration, Examples 1 to 6 had a ΔE of 20 or less after 8 hours at 120°C, which shows that discoloration in a thermal environment is suppressed. In terms of moldability, the resistance value at the time of release of the molded article is 1 MPa or less, and the composition has an extremely low possibility of the molded article deforming or adhering during release even in continuous molding. In addition, when Examples 1 to 5 using a phosphorus-based antioxidant having a pentaerythritol diphosphite skeleton are compared with Example 6 using a phosphorus-based antioxidant that does not have a pentaerythritol diphosphite skeleton, it is found that the former has better snap-fit properties, thermal discoloration properties, and moldability (releasability).
[0041] On the other hand, Comparative Examples 1 to 4 partially satisfy the characteristics, but Comparative Example 1 has a molded article with a resistance value of 5 MPa when released from the mold, and the molded article may remain during continuous molding without being released, which is not preferable. Comparative Example 2 has a ΔE of 26 after 8 hours at 120°C, and discoloration is large when placed in a hot environment, which is not preferable for an appearance part. Comparative Example 3 has a flame retardancy rating of V-2 at a thickness of 0.4 mm, and it is difficult to say that it has sufficient flame retardancy. Finally, Comparative Example 4 has a tensile elongation of 17%, and is not preferable because it cannot suppress brittle fracture due to insufficient snap fit. [Industrial Applicability]
[0042] The flame-retardant polyamide resin composition of the present invention is suitable for molded articles having hinge portions, and the obtained molded articles have excellent snap fit properties and can therefore be suitably used for electrical / electronic parts, automobile parts, and the like in which excellent snap fit properties are desired.
Claims
1. The composition contains 97.5 to 94.5 parts by mass of a polyamide resin (A) and 2.5 to 5.5 parts by mass of a melamine cyanurate (B), the polyamide resin (A) being in a ratio of 50 to 80 parts by mass of a polyamide 66 resin (A-1) and 15 to 45 parts by mass of a polyamide 6 resin (A-2), and contains 0.01 to 1 part by mass of a phosphorus-based antioxidant (C), 0.01 to 1 part by mass of a hindered phenol-based antioxidant (D), and 0.1 to 0.8 part by mass of a fatty acid metal salt-based lubricant (E) relative to a total of 100 parts by mass of the components (A) and (B), 1. A flame-retardant polyamide resin composition, wherein the phosphorus-based antioxidant (C) is a compound having a pentaerythritol diphosphite skeleton.
2. 2. The flame-retardant polyamide resin composition according to claim 1, wherein the fatty acid metal salt-based lubricant (E) is a metal salt of an aliphatic carboxylic acid having 22 to 30 carbon atoms.
3. 3. A molded article having a hinge portion, comprising the flame-retardant polyamide resin composition according to claim 1.
4. The molded product according to claim 3, wherein the molded product having the hinge portion is any one of a ferrite core cover, a cable tie, and an electric wiring protection member.
Citation Information
Patent Citations
Continuous laminated sheet and its preparation
JP1983025379A
Electrophotographic receptor
JP1983035541A
Flame retardant polyamide resin composition
JP1995018179A
Connector with polyamide resin hinge
JP1999026060A
Flame-retardant polyamide resin composition and manufacturing method therefor
JP2003301104A
Cited By
Flame-retardant polyamide resin composition and molded article comprising same
JPWO2022158383A1